Simplifying
2ab + 4ab = 0
Combine like terms: 2ab + 4ab = 6ab
6ab = 0
Solving
6ab = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Divide each side by '6'.
ab = 0
Simplifying
ab = 0
Answer:
11
Step-by-step explanation:
5m - 9 = 4m + 2
Subtract 4m and add 9 to both sides:
m = 11
Answer:
B. {-2, 0, 1, 3}
Step-by-step explanation:
See attached image.
(n-2)multiple 180 degrees the formula for finding the sum of all angles in a polygon regular here n represents the number of sides of the polygon.